Peningkatan Pengetahuan Tentang Tanaman Obat Keluarga Kepada Siswa SDN 19 Kota Bengkulu - Suhli, Noviona Rahma; hari saputri, puji; Susanti, Yesi; Elvia, Rina (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to explore the implementation of Family Medicinal Plants (TOGA) in education at SDN 19 Kota Bengkulu, focusing on improving students’ understanding of health benefits and its contribution to preserving local culture and biodiversity. The research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, direct observation, and documentation of activities involving students, and teachers. The results indicate that students have a good understanding of TOGA and began applying the knowledge in their daily lives, such as using medicinal plants for minor health issues. The TOGA program also plays an important role in preserving local culture and biodiversity, although challenges such as practical skills in plant care and reliance on external assistance were encountered. The study recommends providing further training and enhancing supporting facilities to sustain the TOGA program at SDN 19 Bengkulu City.